Ternary Cross-Modal Interactions between Sweetness, Aroma, and Viscosity in Different Beverage Matrices - Anne Sjoerup Bertelsen; Line Ahm Mielby; Derek Victor Byrne; Ulla Kidmose (Foods, 2020)
Sugar reduction in food and beverage products involves several challenges. Non-nutritive sweeteners may give unwanted off-flavors, while sugar-reduced products often lack mouthfeel. To overcome this, the addition of aroma to increase sweetness through cross-modal interactions, and the addition of hydrocolloids such as pectin to increase viscosity, have been suggested as strategies to aid sugar reduction. However, viscosity has been shown to decrease both taste and aroma intensities. An increase in viscosity may thereby affect the use of aromas as sweetness enhancers. Additionally, the effects of aromas and hydrocolloids on sweetness intensity and mouthfeel depend on the food matrix involved. The present study investigated cross-modal aroma–sweetness–viscosity interactions in two beverage matrices: water and apple nectar. The perceptual effects of vanilla aroma (0–1 mL/kg), sucrose (2.5%–7.5% w/w) and pectin (0%–0.3% w/w) were studied in both matrices. For each matrix, cross-modal interactions were analyzed with descriptive analysis using a trained sensory panel. The effect of vanilla aroma on sweetness intensity was found to be higher in apple nectar compared to in water. Furthermore, pectin affected neither taste, aroma, nor the cross-modal effects of aroma on taste in either of the matrices. These results indicate that pectin, in the studied range of concentrations, may be used to improve mouthfeel in sugar-reduced beverages, without compromising taste or aroma perception.